SUSTAINABILITY OF PHRASEOLOGICAL IMAGE IN DISCOURSE - Naciscione, Anita (International Journal of English Studies, 2009)
In discourse a phraseological unit may extend across sentence boundaries, constituting a continuity. The sustainability of a phraseological unit is the spread of its image in the interrelated web of discourse. A sustained phraseological image provides for the semantic and stylistic cohesion of the text. My aim is to ascertain sustainability as one of the basic concepts of the stylistic use of phraseological units and prove that a sentence-bound approach and thinking fail to account for sustained figurative use. The analysis is based on D.H. Lawrence’s short story "Rawdon’s Roof’. As the story unfolds, the phraseological unit under one’s roof appears sixteen times, undergoing creative changes and acquiring new associations and figurative ties in discourse. It first appears in core use while further in the text new patterns emerge - puns and extended metaphors, subtly interwoven with reiteration of the image-bearing constituent roof or the whole phraseological unit, which becomes the key image by force of sustained reference to it. It is also used in the title, lending an overtone and spanning the boundaries of the short story. Sustained figurative use calls for enhanced cognitive skills of perception, comprehension and interpretation.